New studies in the synthesis and applications of pteridines - Mc Donald, Thomas (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
The work described in this thesis involved the study of two distinct areas of research within pyrimidine and pteridine chemistry. The first of these involved investigation of the pteridine biosynthetic pathway within the zebrafish (Danio rerio). The use of zebrafish for the study of embryonic development in vertebrates is a relatively new area of research, but this species is fast replacing Drosophila as the genetic model of choice aroimd the world today. The neural crest is responsible for some of the most important cells and developmental aspects of all vertebrates including humans.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin